High salinity tolerance of the Red Sea coral Fungia granulosa under desalination concentrate discharge conditions: an in situ photophysiology experiment - van der Merwe, Riaan; Röthig, Till; Voolstra, Christian R.; Ochsenkühn, Michael A.; Lattemann, Sabine; Amy, Gary L. (Frontiers in Marine Science, 2014)
Seawater reverse osmosis desalination concentrate may have chronic/acute impacts on the marine ecosystems in the near-field area of the discharge. Environmental impact of the desalination plant discharge is supposedly site- and volumetric specific, and also depends on the salinity tolerance of the organisms inhabiting the water column in and around a discharge environment. Scientific studies that aim to understand possible impacts of elevated salinity levels are important to assess detrimental effects to organisms, especially for species with no mechanism of osmoregulation, e.g. presumably corals. Previous studies on corals indicate sensitivity towards hypo- and hyper-saline environments with small changes in salinity already affecting coral physiology. In order to evaluate sensitivity of Red Sea corals to increase salinity levels, we conducted a long-term (29 days) in situ salinity tolerance transect study at an offshore seawater reverse osmosis discharge on the coral Fungia granulosa. While we measured a pronounced increase in salinity and temperature at the direct outlet of the discharge structure, effects were indistinguishable from the surrounding environment at a distance of 5 m. Interestingly, corals were not affected by varying salinity levels as indicated by measurement of the photosynthetic efficiency. Similarly, cultured coral symbionts of the genus Symbiodinium displayed remarkable tolerance levels in regard to hypo- and hypersaline treatments. Our data suggest that increased salinity and temperature levels from discharge outlets wear off quickly in the surrounding environment. Furthermore, Fungia granulosa seem to tolerate levels of salinity that are distinctively higher than reported for other corals previously. It remains to be determined whether Red Sea corals in general display increased salinity tolerance, and whether this is related to prevailing levels of high(er) salinity in the Red Sea in comparison to other oceans.